Ring-Fencing in Europe The EU's Bank Structural Reform and a Legal Comparative Look at National Legislation in Europe's Three Financial Capitals - Oppolzer, Konstantin (Studien zum Bank-, Börsen- und Kapitalmarktrecht, 2019)
This dissertation explores structural reforms for banks that stipulate the separation of deposit-taking and other services considered vital to the real economy from certain investment banking activities deemed particularly risky with the aim of, inter alia, mitigating systemic risk and the too-big-to-fail problem. These structural reforms can collectively be referred to as "ring-fencing". The focus of the dissertation is on the legal developments on a European Union level and in the United Kingdom, Germany and Switzerland, which are home to Europe's most important financial centres. The dissertation is divided into three parts: In its first part, it establishes a concept and a definition of ring-fencing that allow to distinguish it from related bank structural reforms. In its second part, it assesses legislative steps already taken in the European Union and the withdrawal of the file by the European Commission and discusses potential alternatives for installing a union-wide ring-fence. In its third part, a legal comparative analysis is conducted, discussing conceptual differences in national bank structural reform legislation in the United Kingdom, Germany and Switzerland and exploring whether the countries adopted legislation that matches the concept and definition of ring-fencing established in the first part. Altogether, the dissertation contributes to the terminology and classification of existing and future ring-fencing initiatives and paints a comprehensive picture of current developments and prospects on EU level. It furthermore highlights structural differences of national approaches of Europe's three most important financial centres, and casts light on Switzerland's unique yet barely recognized ring-fencing efforts.